1999
DOI: 10.1007/s004670050710
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological spectrum of septicemia and peritonitis in nephrotic children

Abstract: From April 1993 to December 1997, 452 admissions of 231 children with nephrotic syndrome to Chang Gung Children's Hospital were retrospectively reviewed. There were 10 episodes of sepsis and 8 episodes of peritonitis in 18 children, and 14 microorganisms were cultured. Two children died due to Streptococcus pneumoniae sepsis. Gram-positive microorganisms (n=7) and Gram-negative microorganisms (n=7) were found in equal numbers. Enterococcus (1), Streptococcus pneumoniae (4), group D streptococcus (1), and Strep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 15 publications
1
23
0
Order By: Relevance
“…24 Peritonitis due to penicillin resistant pneumococci are increasingly reported in children with nephrotic syndrome. 18 Both pneumococcal isolates were resistant to penicillin in our study. The E coli isolate was multidrug resistant.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…24 Peritonitis due to penicillin resistant pneumococci are increasingly reported in children with nephrotic syndrome. 18 Both pneumococcal isolates were resistant to penicillin in our study. The E coli isolate was multidrug resistant.…”
Section: Discussionsupporting
confidence: 50%
“…Chang-ching wei et al and Tain YL also had similar findings in their studies. 10,17,18 MRSA and CONS, the causative agents of septicemia in present study were not the frequently reported pathogens in nephrotic syndrome. In the study by Ajeyan et al, MRSA was isolated in 2 children.…”
Section: Discussionmentioning
confidence: 43%
“…The infectious complications, especially primary peritonitis, are well-known alarming situation in children with nephrotic syndrome (NS) [3,6,7,17,18]. Peritonitis has been reported with an incidence of 1.5-16% in nephrotic children [3,4,6,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…There is a tendency to development of infections, especially caused by capsulated bacteriae like S. pneumoniae and H. influenzae, in nephrotic patients due to various risk factors including reduced immunoglobulin concentration via urinary loss of IgG, depletion of properdin factor B, the deleterious effects of edematous tissue resembling culture medium, decreased bactericidal activity of leukocytes by immunosuppressive therapy and inefficient perfusion of spleen due to hypovolemia (1)(2)(3)(4). Case history, clinical and laboratory evaluation and 4 year-follow up of our patient disclosed a tendency to development of infections particularly peritonitis.…”
Section: Discussionmentioning
confidence: 99%
“…Several factors may explain the tendency of nephrotic children to develop bacterial infections: low IgG levels due to impaired synthesis or urinary loss, urinary loss of Factor B and impaired cellular immunity (1,2).…”
Section: Introductionmentioning
confidence: 99%